Effect of potential oocyte transport protocols on blastocyst rates after intracytoplasmic sperm injection in the horse. (December 2013) - Foss, R.; Ortis, H.; Hinrichs, K.
Summary: Reasons for performing study: Intracytoplasmic sperm injection (ICSI) is used to produce foals from otherwise infertile mares and from stallions with limited sperm stores, but requires expensive equipment and is technically demanding. Methods to transport oocytes to ICSI laboratories would allow collection of oocytes by the referring veterinarian and enable greater application of this technique. Objectives: This study was conducted to evaluate protocols that could be used to transport immature and maturing oocytes for ICSI. Study design: In vitro experiment. Methods: Oocytes were recovered by transvaginal ultrasound‐guided follicular aspiration either from dominant follicles 24 h after deslorelin administration (dominant stimulated follicle [DSF]), or from subordinate (immature) follicles at the same time. To mimic transport, DSF oocytes were incubated overnight under differing conditions before ICSI; immature oocytes were placed in varying conditions overnight before in vitro maturation, followed by ICSI. The rate of blastocyst production was compared among treatments. Results: Blastocysts were produced in all groups. Dominant stimulated follicle oocytes held in sealed tubes in pre‐equilibrated control maturation medium maintained at 37°C yielded blastocyst development equal to that obtained for control incubated oocytes (70%). Dominant stimulated follicle oocytes held similarly in a warm passive device yielded poor blastocyst development (10%). Immature oocytes held for one or 2 nights in modified M199 medium, or for one night in commercial embryo holding solution, in air at room temperature, yielded 35–37% blastocyst development per injected oocyte. Conclusions: A commercially available medium can be used for shipping immature oocytes at room temperature with good resulting blastocyst rates. Better blastocyst rates per oocyte are obtained from DSF oocytes; however, these require maintenance at 37°C and as they are already maturing at the time of collection, are more sensitive to delays. This new, practical information supporting transport of both immature and DSF oocytes for ICSI may allow wider use of this procedure.